2021
DOI: 10.4269/ajtmh.19-0858
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Patients with Visceral Leishmaniasis: Case Report and Literature Review

Abstract: The diagnosis of visceral leishmaniasis (VL) is complicated and often unsuspected. Little is known of the usefulness of nuclear imaging in VL. Our objective was to describe findings seen in fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) in cases of VL. We retrospectively reviewed VL cases diagnosed at Vall d’Hebron University Hospital from May 2012 to May 2018 and selected those that had an FDG-PET/CT performed. Information on procedures and details of the FDG-PET/CT features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Thus, iron overload with hepatosplenomegaly detected in this study may reflect the severe conditions in the Leishmania infection and its associated HLH. Several studies have demonstrated the pattern of Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (F18 FDG-PET/CT) in the visceral leishmaniasis [27][28][29]. Diffuse splenic and bone marrow uptake of FDG is the main feature in the VL patients, and VL associated HLH cases presented more significantly elevated diffuse uptake in the liver, spleen and spinal column.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, iron overload with hepatosplenomegaly detected in this study may reflect the severe conditions in the Leishmania infection and its associated HLH. Several studies have demonstrated the pattern of Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (F18 FDG-PET/CT) in the visceral leishmaniasis [27][28][29]. Diffuse splenic and bone marrow uptake of FDG is the main feature in the VL patients, and VL associated HLH cases presented more significantly elevated diffuse uptake in the liver, spleen and spinal column.…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT is valuable in the diagnosis of fever of unknown origin, but there is little information on the diagnosis potential of FDG-PET/CT in VL, especially in immunocompromised patients. PET/CT shows that most VL patients had increased spleen FDG uptake, and some patients have bone marrow and lymph node FDG uptake ( Pinnegar et al., 2021 ). Bone marrow and lymph node uptake are more likely to occur in immunocompetent patients than in immunocompromised patients ( Pinnegar et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT shows that most VL patients had increased spleen FDG uptake, and some patients have bone marrow and lymph node FDG uptake ( Pinnegar et al., 2021 ). Bone marrow and lymph node uptake are more likely to occur in immunocompetent patients than in immunocompromised patients ( Pinnegar et al., 2021 ). Two different patterns of spleen FDG uptake in VL patients have been defined on PET/CT examination: diffuse and focal ( Zanoni et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations